Study on Block Device Driver and NVMe their Implementation Impacts on Performance - Kharch, Raman Kumar; Katkar, Vijay D; Kulkarni, Kedar (International Journal of Computer Sciences and Engineering, 2025)
Solid-State Drive (SSD) is also known as Solid-State Disk it contains no moving components. Attraction for SSD is due to its high throughput and scalability. It distinguishes from traditional magnetic disks like hard disk drives which contains movable head and spinning disk. SSDs are electronic circuit built on NAND-Flash/NOR-Flash and PCM. Solid-State Drive uses non-volatile memory for storage and retrieval of data or information in the form of sectors and/or pages and shows better performance than hard disks. Maximum IO performance of the used memory technology can be achieved using a properly written software device driver, which can effectively utilizes underlying hardware resources and extracts the maximum performance from the storage device. This paper is a survey on key literature on IO performance of SSD and block driver. It deals with the effort that defines what characteristics an effective solid state drive should have. The paper also discusses trends and categories in research and questions that are further open for investigation.